Heart Caring "Handy" - Prototype - Retnasamy, Vithyacharan; R., Vijenthi; Sazali, Yaacob, Prof. Dr.; R., Nagarajan; Rizon, Juhari; Kenneth, Sundaraj; Shukry, Abd. Majid; Mohamad Hanif, Abd Hamid (Malaysian Invention and Design Society (MINDS), 2010)
R. Charan and his team won bronze for Heart Caring "Handy" - Prototype at ITEX 2006, 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.